Application of Biomorphic Concepts in the Design and Development of the Banggai Port Terminal in Banggai Laut Regency - Yayu Marliani S; Nashrah Arsyad; Andi Muhammad Ikhsan (Journal of Creative Power and Ambition (JCPA), 2026)
Banggai Laut Regency is an archipelagic area, where the presence of ports plays a strategic role as the main hub for passenger mobility, logistics distribution, and inter-island connections. This terminal is classified as a collecting port, but the increase in operational activity intensity over the past few years has not been matched by adequate capacity and quality of facilities. This situation has led to several architectural problems, including limited waiting room capacity, circulation conflicts between passengers, vehicles, and goods, as well as suboptimal provision of supporting facilities that meet port service standards. The aim of this study is to analyze the application of biomorphic concepts in the design development of Banggai Port in Banggai Laut Regency. To achieve the research objectives, a descriptive method with qualitative and quantitative approaches was used. Data collection was carried out through field observations, interviews with relevant parties, as well as a literature review of regulations, technical standards, and relevant literature. The results of the analysis indicate that the design concept  which adopts a biomorphic architectural approach through form transformations inspired by the morphology of the Banggai Dragonet (Pterapogon kauderni), an endemic species of Banggai Laut Regency  is feasible. This approach is combined with a visual interpretation of ocean wave rhythms as a representation of the coastal area’s character.